The Experiences of Ghanaian Midwives on the Use of Nonadjustable Delivery Beds: A Qualitative Study - Anita F. Dartey PhD, MNursing, OHNP, RN; Gladys Dzansi PhD, MPhil, RN; Constancia Atachie MPhil, BA, RM, RN1; Evelyn Sunnu PNS, MPH, BA, RN; Felix K. Nyande PhD, MPhil, BA, RN (SAGE Publishing, 2021)
Background Hospital beds are of great assistance to both clients and caregivers as they give lots of choices to the users. More often, clients have difficulty getting in and out of beds, but the adjustable features of the beds make it possible for them to be comfortable, regardless of their condition. This situation may not be the same if nonadjustable delivery beds (NADBs) are used in conducting deliveries at health care facilities. This study explored the experiences of midwives using NADBs in selected Christian Health Association of Ghana (CHAG) hospitals in the Volta Region of Ghana. Methods The study employed an exploratory qualitative research design with purposive sampling. Semistructured interview data were audio recorded. The inclusion criteria were professional midwives with at least 1 year of working skills and the midwives should have conducted deliveries using NADBs during their practice. Data were collected concurrently with data transcription and analyzed using content analysis. Saturation was reached after the 20th interview. Results Three themes emerged from the study: NADBs not comfortable to work with, assumption of awkward postures, and the nature of the delivery beds. Conclusion The findings of the study show that midwives experience several setbacks in the use of NADBs in conducting deliveries as they sacrifice their health for work.